State of Art Update: Detection and Classifi cation of Early Colonic Neoplasia - K McWhirter; R George; Y Ang (Archives of Clinical Gastroenterology - Peertechz Publications, 2017)
Colonoscopy has been shown to be effective in the detection and removal of precancerous lesions and early cancers, and as a result, colorectal screening programs are in preparation, or in place throughout  the world. Screening efforts are reducing the incidence of colorectal cancer (CRC) and allow diagnosis CRCs at an earlier stage. It is increasingly evident that colonoscopic polypectomy including endoscopic mucosal resection and submucosal dissection has become a means of cancer prevention with evidence of reduced predicted incidence and mortality of colorectal malignancies. However, the risk of interval CRC relates to the skill of the performing colonoscopist, rather than any patient or polyp characteristic. Every endoscopist needs to actively look for proximal and fl at or depressed lesions. For the general  endoscopist, this means the ability to fi nd and accurately assess a lesion is vital. In addition, advancing endotherapeutics means more lesions are potentially removable, and so endoscopists must be able to describe lesions in a standard fashion. This review deals with the current means of describing lesion morphology and surface characteristics, together with the signifi cance of these. We also discuss the developing adjuncts to endoscopic imaging.